Analisis Komunikasi Persuasif Capres 2024 Dalam Debat KPU (Kajian Retorika Aristoteles) - Hapsari, Natalia Endah; Fatinova, Dede; Ardan, Fariz (DAS Institute, 2025)
The aim of this study is to uncover the political rhetoric of the capres in the 2024 elections according to the analysis of the ethos, pathos and logos of Aristotle. To obtain results, this study uses qualitative research methods. For the primary data, the research is derived from videos posted on social media by each couple of capres and cawapres during the 2023 presidential election campaign, while the secondary data sources are obtained from articles and books related to Aristotle's rhetoric. Whereas the data collection technique used for this research is a recording and recording technique. The data obtained will then be digested according to Aristotle's rhetorical theory of ethos, pathos, logos. The results of the research revealed that Capres Anies Baswedan was more dominant with the logos element which meant more giving facts and data in the argument. While Prabowo Subianto tends to be strong with the element of pathos with the dominant emotional side. While Ganjar Pranowo provides a balanced portion for the elements of pathos and logos.